If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + -4k = -3k Solving 23 + -4k = -3k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '3k' to each side of the equation. 23 + -4k + 3k = -3k + 3k Combine like terms: -4k + 3k = -1k 23 + -1k = -3k + 3k Combine like terms: -3k + 3k = 0 23 + -1k = 0 Add '-23' to each side of the equation. 23 + -23 + -1k = 0 + -23 Combine like terms: 23 + -23 = 0 0 + -1k = 0 + -23 -1k = 0 + -23 Combine like terms: 0 + -23 = -23 -1k = -23 Divide each side by '-1'. k = 23 Simplifying k = 23
| 62x+87-6015=43424 | | x+3w+x+3w=96 | | 24+16=24x-10 | | 24-8=8-2x | | 24+8=8+2x | | 8x=7x+12 | | 4x=456 | | x^4+4x^3+2x^2-x=6 | | 3p-7g+14p= | | .18(6)+0.03x=.09(24+x) | | X+1.5(x+2)=58 | | 5+3x-7= | | 10n+15n= | | 4[2x-(3-x)+5]=6x-28 | | x/5=4x+1 | | 50x+5897-4312=386135 | | 243=9(10+x) | | 2+u=0 | | 3(3x-2)-5x=x-3 | | 0.10+0.05(52-x)=450 | | (X+2)7=40 | | 6y+1=3x+1 | | 28w-12=16w-30 | | 3r^2-2r-3=0 | | 6x-16=4x+30 | | x^2-5xy+6y^2=0 | | (7x-2)(-5x+6)= | | a^2+14a-99=0 | | -2m-5m=9m-12 | | 7n+1=2n-4 | | -x+19+3x+19=4 | | 50+2x=120-5x |